Preparation method of copper-doped polymer self-assembled nano-particles and nano-particles prepared by same

By self-assembly constructing functional nanoparticles, the copper ions are coordinated with ammonia, the problem of low ammonia storage and release efficiency in the prior art is solved, and efficient and stable ammonia storage and release effects are achieved.

CN119842084AActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311336768.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

The prior art has problems such as low storage capacity and irreversible absorption in terms of ammonia storage and release, making it difficult to achieve safe and efficient ammonia storage and release.

Method used

By constructing functional nanoparticles using self-assembly, copper ions are brought into the particles to form a copper-ammonia composite structure, and the ammonia and copper ions are coordinated by hydrogen bonds or van der Waals forces to achieve efficient adsorption and rapid release of ammonia.

Benefits of technology

It has achieved high-efficiency ammonia storage and good stability of copper-doped polymer self-assembled nanoparticles, which can quickly release ammonia under heating conditions, and has a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842084A_ABST
    Figure CN119842084A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of copper-doped polymer self-assembled nano-particles and the nano-particles prepared by the preparation method. Comprising the following steps: mixing raw materials containing a solvent A, a copper salt and non-conjugated polyimide, adding a solvent B, filtering the obtained precipitate, and drying to obtain the copper-doped polymer self-assembled nanoparticles. The preparation method is simple, low in cost, short in period and high in yield; the copper-doped polymer self-assembled nanoparticles are stable in structure, good in ammonia adsorption and desorption cycling stability and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing copper-doped polymer self-assembled nanoparticles and the prepared nanoparticles, belonging to the field of functional nanomaterials. Background Art

[0002] Ammonia (NH3) has attracted much attention as a carbon-free hydrogen storage compound. However, NH3 is a highly corrosive gas that is difficult to handle and store. Currently, ammonia can be stored in pressure-resistant containers by liquefying at temperatures far below freezing, or by physical adsorption on porous compounds such as activated carbon, zeolites, and metal-organic frameworks (MOFs), but there are problems such as low storage capacity and irreversible absorption. Therefore, a functional material that can safely and efficiently store and release ammonia has become a research hotspot.

[0003] Metal-doped polymer self-assembled nanoparticles can effectively solve this problem. Self-assembly refers to the spontaneous formation of a structure with unique characteristics through the interaction between molecules, so that a single molecule forms a directional and ordered structure. The units are orderly connected through non-covalent bonds to form an assembly with a specific structure or function. At present, it has shown great application potential in the fields of biology, chemistry, physics, and medicine. Summary of the invention

[0004] By using self-assembly to construct functionalized nanoparticles, on the one hand, copper ions can be brought into the interior of the particles under the interaction of hydrogen bonds or van der Waals forces. At the same time, copper ions can retain binding sites for reacting with ammonia, and ammonia can coordinate with copper ions to form a copper-ammonia composite structure. On the other hand, under heating conditions, ammonia can be quickly separated from copper ions and released into the environment. Therefore, metal-doped polymer self-assembled nanoparticles have broad application prospects in the fields of ammonia storage and hydrogen production, VOCs gas detection and adsorption.

[0005] According to one aspect of the present application, a method for preparing copper-doped polymer self-assembled nanoparticles is provided, comprising the following steps:

[0006] The raw materials containing solvent A, copper salt and non-conjugated polyimide are mixed, and solvent B is added. The obtained precipitate is filtered and dried to obtain the copper-doped polymer self-assembled nanoparticles.

[0007] The solvent A is selected from at least one of DMSO, methanol, ethanol, water and acetone;

[0008] The copper salt is selected from at least one of copper chloride, copper nitrate and copper sulfate.

[0009] The mass ratio of the copper salt to the non-conjugated polyimide is 0.1 to 50:1;

[0010] The mass ratio of the copper salt to the solvent A is 0.01 to 1:10.

[0011] The molecular weight of the non-conjugated polyimide is 7000-15000Da;

[0012] The end-capping group of the non-conjugated polyimide is a carboxyl group;

[0013] The non-conjugated polyimide contains carboxyl side groups;

[0014] The non-conjugated polyimide is obtained by the following method:

[0015] Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer;

[0016] The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid;

[0017] The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine;

[0018] The reaction temperature is 80-260°C;

[0019] The reaction atmosphere is an inert gas atmosphere.

[0020] The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1.

[0021] The reaction is a melt polymerization reaction.

[0022] The reaction time is 0.5 to 6 hours.

[0023] The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

[0024] Optionally, the molecular weight of the non-conjugated polyimide is 1000-15000 Da.

[0025] Optionally, the non-conjugated polyimide is selected from poly-N-(3-phenyl)-2-carboxymethylimide-succinimide, poly-N-ethyl-2-carboxymethylimide-succinimide, polyphenyl oxalic acid diimide, polyethyl oxalic acid diimide, polyethyl glutaric acid diimide, polyphenyl glutaric acid diimide, polyethyl succinic acid diimide, polyphenyl succinic acid diimide with carboxylic acid as side groups and end groups;

[0026] The solvent B is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane;

[0027] The volume ratio of the solvent A to the solvent B is 0.1 to 1:10.

[0028] Specifically,

[0029] (1) dispersing a low molecular weight non-conjugated polyimide having a self-assembly function and a carboxylic acid group as a side group and a capping group and a divalent copper salt in a first solvent and uniformly stirring;

[0030] (2) gradually adding a second solvent until a precipitate is generated, filtering the resulting precipitate and drying it, thereby obtaining copper-doped polymer self-assembled nanoparticles with high-efficiency ammonia storage performance;

[0031] According to another aspect of the present application, there is provided a copper-doped polymer self-assembled nanoparticle prepared by the above-mentioned method for preparing copper-doped polymer self-assembled nanoparticles.

[0032] According to another aspect of the present application, there is provided an application of the above-mentioned copper-doped polymer self-assembled nanoparticles for use in the field of ammonia storage.

[0033] Copper ions can be fixed by interacting with low molecular weight polyimide and carbonyl groups on carboxylic acid side groups. When non-conjugated polyimide self-assembles to form nanoparticles under hydrogen bonding or van der Waals force interactions, copper ions are brought into the particles. At the same time, copper ions retain binding sites with ammonia. When ammonia is present in the environment, ammonia can coordinate with copper ions to form a copper-ammonia composite structure in the particles. When heated, ammonia can quickly separate from copper ions and be released into the environment.

[0034] The beneficial effects of this application include:

[0035] (1) The preparation method is simple, low cost, short cycle and high yield;

[0036] (2) The copper-doped polymer self-assembled nanoparticles have a stable structure, good cyclic stability of ammonia adsorption and desorption, and a long life. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the fluorescence change diagram of poly N-(3-phenyl)-2-carboxymethylimide-succinimide before and after copper doping.

[0038] Figure 2 This is the XRD spectrum of poly N-(3-phenyl)-2-carboxymethylimide-succinimide in Example 1.

[0039] Figure 3 This is the XRD spectrum of copper-doped poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide in Example 1.

[0040] Figure 4This is the XRD spectrum of the copper-doped poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide after absorbing ammonia in Example 1.

[0041] Figure 5 This is the ammonia absorption cycle spectrum of copper-doped poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide in Example 1. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited thereto.

[0043] Example 1

[0044] 0.3 g of poly (N-(3-phenyl)-2-carboxymethylimide-succinimide) with an average molecular weight of 7000 Da was dissolved in 3 mL of dimethyl sulfoxide (DMSO) at room temperature and stirred evenly for 5 minutes. Subsequently, 0.3 g of cupric chloride dihydrate was added and stirring was continued for 30 minutes. Then, 30 mL of ethanol was added to produce a precipitate. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 65%.

[0045] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 115% of the bulk weight after 48 hours.

[0046] Figure 1 The fluorescence change diagram of poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide before and after copper doping is shown in the figure. It can be seen from the figure that copper ions are successfully doped into the polymer and quench its fluorescence.

[0047] Figure 2 This is the XRD spectrum of poly N-(3-phenyl)-2-carboxymethylimide-succinimide in Example 1. It can be seen from the figure that it has an amorphous structure.

[0048] Figure 3 This is the XRD spectrum of copper-doped poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide in Example 1. It can be seen from the figure that the structure does not change significantly after copper is added, and copper is doped in the form of ions rather than oxides.

[0049] Figure 4 This is the XRD spectrum of copper-doped poly (N-(3-phenyl)-2-carboxymethylimide)-succinimide after ammonia absorption in Example 1. From the figure, it can be seen that the 2θ peak moves to a larger angle, indicating that its structure changes after amino group adsorption.

[0050] Figure 5This is the ammonia absorption cycle spectrum of copper-doped poly N-(3-phenyl)-2-carboxymethylimide-succinimide in Example 1. It can be seen from the figure that copper-doped poly N-(3-phenyl)-2-carboxymethylimide-succinimide has good ammonia adsorption and release capabilities and is a good solid ammonia storage material.

[0051] Example 2

[0052] 0.3 g of poly (N-ethyl-2-carboxymethylimide-succinimide) with an average molecular weight of 7000 Da was dissolved in 5 mL of methanol at room temperature and stirred evenly for 5 min. Subsequently, 0.75 g of cupric chloride dihydrate was added and stirring was continued for 30 min. Then, 50 mL of acetonitrile was added to produce a precipitate. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 68%.

[0053] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 112% of the weight after 48 hours.

[0054] Example 3

[0055] 0.3 g of polyphenyl oxalic acid diimide with an average molecular weight of 7000 Da was dissolved in 5 mL of ethanol at room temperature and stirred evenly for 5 minutes. Subsequently, 1.5 g of cupric chloride dihydrate was added and stirring was continued for 30 minutes. Then, 50 mL of chloroform was added to produce precipitation. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 73%.

[0056] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 118% of the weight after 48 hours.

[0057] Example 4

[0058] 0.3 g of poly(ethyl oxalic acid diimide) with an average molecular weight of 7500 Da was dissolved in 5 mL of water at room temperature and stirred evenly for 10 min. Then 0.3 g of copper nitrate was added and stirring was continued for 40 min. Then 30 mL of acetone was added to produce a precipitate. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity. The yield was 68%.

[0059] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 121% of the weight after 48 hours.

[0060] Example 5

[0061] 0.3 g of poly(ethylglutaric acid diimide) with an average molecular weight of 7500 Da was dissolved in 5 mL of acetone at room temperature and stirred evenly for 10 min. Then 0.75 g of copper nitrate was added and stirring continued for 40 min. Then 30 mL of toluene was added to produce precipitation. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity. The yield was 72%.

[0062] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 117% of the weight after 48 hours.

[0063] Example 6

[0064] 0.3 g of polyphenylglutaric acid diimide with an average molecular weight of 7000 Da was dissolved in 5 mL of dimethyl sulfoxide (DMSO) at room temperature and stirred evenly for 10 minutes. Subsequently, 1.5 g of copper nitrate was added and stirring was continued for 40 minutes. Then, 50 mL of toluene was added to produce precipitation. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 75%.

[0065] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 113% of the weight after 48 hours.

[0066] Example 7

[0067] 0.3 g of poly(ethyl succinic acid diimide) with an average molecular weight of 7000 Da was dissolved in 5 mL of methanol at room temperature and stirred evenly for 5 minutes. Subsequently, 0.3 g of copper sulfate was added and stirring continued for 30 minutes. Then, 50 mL of acetonitrile was added to produce a precipitate. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 71%.

[0068] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 117% of the weight after 48 hours.

[0069] Example 8

[0070] 0.3 g of polyphenyl succinic acid diimide with an average molecular weight of 7500 Da was dissolved in 5 mL of dimethyl sulfoxide (DMSO) at room temperature and stirred evenly for 5 minutes. Subsequently, 1.5 g of copper sulfate was added and stirring continued for 30 minutes. Then, 50 mL of ethanol was added to produce a precipitate. The precipitate was filtered and dried to obtain copper-doped polymer self-assembled nanoparticles with high ammonia storage capacity, with a yield of 64%.

[0071] 30 mg of the nanoparticles were added into a pure ammonia gas environment, and the adsorption amount could reach 121% of the weight after 48 hours.

[0072] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing copper-doped polymer self-assembled nanoparticles, characterized in that: The following steps are involved: The raw materials containing solvent A, copper salt and non-conjugated polyimide are mixed, and solvent B is added. The obtained precipitate is filtered and dried to obtain the copper-doped polymer self-assembled nanoparticles.

2. The preparation method according to claim 1, characterized in that: The solvent A is selected from at least one of DMSO, methanol, ethanol, water and acetone; The copper salt is selected from at least one of copper chloride, copper nitrate and copper sulfate.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the copper salt to the non-conjugated polyimide is 0.1 to 50:1; The mass ratio of the copper salt to the solvent A is 0.01 to 1:

10.

4. The preparation method according to claim 1, characterized in that: The molecular weight of the non-conjugated polyimide is 7000-15000Da; The end-capping group of the non-conjugated polyimide is a carboxyl group; The non-conjugated polyimide contains carboxyl side groups; The non-conjugated polyimide is obtained by the following method: Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer; The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid; The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine; The reaction temperature is 80-260°C; The reaction atmosphere is an inert gas atmosphere; The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1; The reaction is a melt polymerization reaction; The reaction time is 0.5 to 6 hours; The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

5. The preparation method according to claim 1, characterized in that: The solvent B is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane; The volume ratio of the solvent A to the solvent B is 0.1 to 1:

10. 6 . Copper-doped polymer self-assembled nanoparticles prepared by the method for preparing copper-doped polymer self-assembled nanoparticles according to any one of claims 1 to 5 .

7. An application of the copper-doped polymer self-assembled nanoparticles according to claim 6, characterized in that: Used in ammonia storage field.

Citation Information

Patent Citations

  • Transition metal-doped carbon fluorescent quantum dot preparation method

    CN106147760A

  • Nano Fe3O4 in-situ growth N, P co-doped porous carbon negative electrode material and preparation method thereof

    CN111977702A

  • Modified polyimide secondary battery adhesive and preparation method thereof

    CN114709420A

  • Preparation method and application of N-sulfonyl amidine polymer

    CN114805800A

  • Cu-BDC-NH2 material as well as preparation method and application thereof

    CN116675868A